Morphological Variants and Factors Associated With Neural Tube Defects at a Regional Referral Hospital - Benard Owere; Patience D. Nalumaga; Dauglas Nkoyooyo; Innocent Ayesiga (Health Science Reports, 2026)
Background: Neural Tube Defects (NTDs) remain a significant public health concern, especially in low‐resource settings. This study investigated the morphological variants of NTDs and identified factors associated with their development among neonates at Mbarara Regional Referral Hospital (MRRH). Methods: A retrospective cross‐sectional descriptive study was conducted using medical records from January 2022 to December 2024. One hundred and six records of neonates diagnosed with NTDs were included. Data were analyzed using STATA version 17. Bivariate and multivariate logistic regression analyses were performed to assess associations between risk factors and NTD types. Results: Open NTDs accounted for 70.75% of cases, with myelomeningocele being the most common. Most defects were posteriorly located (81.13%). Low birth weight (AOR = 4.09, CI: 1.00–6.67, p = 0.049) and lack of folic acid supplementation (AOR = 7.12, CI: 1.32–8.33, p = 0.022) were significantly associated with open NTDs. Conclusion: Open NTDs are the predominant morphological variant at MRRH. Key risk factors include low birth weight, inadequate folic acid supplementation, and maternal HIV status.
Keywords: Birth weight; Folic acid; Morphological variants; Neural tube defects